Intraperitoneal administration of dexpanthenol inhibits the decrease in the number of leydig and sertoli cells in the wistar strain of white rat (rattus norvegicus) test exposed to monosodium glutamate - Susianingsih Murni Hartati; Wimpie Pangkahila; I Gusti Made Aman (IJAAM (Indonesian Journal of Anti-Aging Medicine), 2018)
Introduction: Free radical accumulation that goes beyond the ability of the body’s defense mechanism causes oxidative stress which is one of the causes of premature aging in the testicular organs. Dexpanthenol works by increasing the levels of intracellular coenzyme A, ATP and glutathione which play a role in the defense and repair of cells against oxidative and inflammatory stress. The purpose of this study was to prove that intraperitoneal administration of Dexpanthenol inhibited the decrease in the number of Leydig cells and Sertoli cells in the testes of Wistar rats (Rattus norvegicus) exposed to Monosodium glutamate (MSG). Methods: This research is true experimental with post-test only control group design. 32 rats were divided into two groups with each group consisting of 16 rats. The first group was the Control Group (P1) which was given a placebo aquadest twice a week intraperitoneally. The second group was the treatment group (P2) which was given Dexpanthenol 1000 mg / kgBW mice twice a week intraperitoneally. All groups were given 4 g / kgBB of MSG mice every day with sonde. The experiment lasted 14 days and then testicular tissue was taken be evaluated and the number of Leydig cells and Sertolinya cells were counted. Results: The Saphiro-Wilk test results showed that the data of the number of Leydig cells was not normally distributed (p <0.05) while the data of the Sertoli cell counts were normally distributed p> 0.05. Comparative analysis of Leydig cell counts was conducted using Mann-Whitney Test while comparative analysis of Sertoli cell numbers using Independent-T Test. The results of the analysis showed that there were significant differences in the mean number of Leydig cells and Sertoli cells between groups P1 and P2. Conclusion: This study concluded that intraperitoneal administration of Dexpanthenol inhibits the decrease in the number of Leydig cells and Sertoli cells in the testis of Wistar strain white rats (Rattus norvegicus) exposed by Monosodium glutamate.